An overview on the use of concentrated growth factor (CGF) and poly lactic-co-glycolic acid (PLGA) in periodontal regeneration / Nur Zety Mohd Noh, Nur Aliana Hidayah Mohamed and Erni Noor. - Mohd Noh, Nur Zety; Mohamed, Nur Aliana Hidayah; Noor, Erni (2019)
Alveolar bone loss as a result of periodontitis and physiological alveolar bone resorption following tooth extraction can be treated and minimized with clinical procedures such as periodontal regeneration and socket preservation. The use concentrated growth factor (CGF) has received an attention nowadays in clinical practice as source of growth factors. Meanwhile, poly lactic-co-glycolic acid (PLGA) microspheres is well known for its use in drug delivery due to its high porosity and interconnected pores. The objective of this review paper is to provide an overview on the current use of CGF and PLGA in periodontal regeneration in order to promote and obtain new bone formation and periodontal attachment.